Korelasi Agama, Filsafat dan Ilmu - Abd Wahid (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Seeking the truth is one of that a man does in his life. Standard of the truth is dependent on media, which is employed by the man. There are there media, which are used by a man in seeking the truth. They are; religion, philosophy, and knowledge or science. Truth provided by religion tends to rely on truth-values that are referred to God. The truth produced by philosophy tends to provide deep reflective thought, which are less connected to God. While the truth afforded by science consists of knowledge values that are inconsistent and changeable following the human life development.